KHIYAR DALAM JUAL BELI DENGAN SISTEM RETUR ANTARA DISTRIBUTOR DAN RESELLER - Oktaviandra, Rio; Fahmi, Moch. Riza; Suhardiman, Suhardiman (Al-Aqad, 2023)
This study aims to determine the practice of reviewing the Compilation of Sharia Economic Law on khiyar in buying and selling with a return system between distributors and resellers of Roti Royal in Sungai Kakap District, Kubu Raya Regency. This research uses a qualitative method with the type of empirical legal research. Data sources use primary data and secondary data in the form of books, journals, theses, and articles. Data collection techniques are interviews and documentation. The data analysis technique used by researchers is to collect data, reduce data, present data, and draw conclusions. The results showed that: 1) The agreement and agreement between the two parties the distributor and the reseller is oral because both parties trust each other and do not harm any party. 2) The review of the Compilation of Sharia Economic Law on khiyar in Sungai Kakap District, Kubu Raya Regency is permissible because it has implemented khiyar 'aib and khiyar conditions. Then, in this sale and purchase the 'aib goods have been explained previously by the distributor and the reseller also knows the physical condition of the goods.